IDENTIFIKASI TUMBUHAN BUNGA ASOKA (Ixora)YANG ADA DI DESA NGEMBALREJO - nurul saidah; Siti Qoidah; Siti Fatimah; Hashina Izzatin Nida; Muhamad Jalil (Institut Agama Islam Negeri Kerinci, 2023)
In Indonesia, the soka plant (Ixora sp.) is an ornamental plant that is quite popular among ornamental plant hobbyists. Besides being unique, the shapes and types also vary. The purpose of this study was to identify the type of flower Ixora sp. located in Ngembal Rejo Village. This research method is descriptive qualitative by observing morphology. The results showed that there were 3 types of Ixora sp flowers. in Ngembalrejo Village, consisting of Ixora javanica, Ixora chinensis) and Ixora coccinia. So, the morphological differences in the soka plant only lie in the color of the flowers. Meanwhile, for the structure of leaves, stems and roots, there is dont difference because they are still in the same family and one genus.